2019
DOI: 10.1002/mgg3.1010
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐by‐gene interactions associated with the risk of conotruncal heart defects

Abstract: Background The development of conotruncal heart defects (CTDs) involves a complex relationship among genetic variants and maternal lifestyle factors. In this article, we focused on the interactions between 13 candidate genes within folate, homocysteine, and transsulfuration pathways for potential association with CTD risk. Methods Targeted sequencing was used for 328 case‐parental triads enrolled in the National Birth Defects Prevention Study (NBDPS). To evaluate the interaction of two genes, we applied a cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Previous studies have also investigated the role of DNMT SNPs in relation to the risk of CHDs. Lyu et al discovered that a SNP pair, including rs11892646 located in the DNMT3A gene and rs56219526 located in the MTRR gene, was associated with a risk of developing a conotruncal heart defect [147]. Further, a study in southeastern Iran found that the AG (heterozygous) genotype at rs6999593 in DNMT1 was strongly correlated with the susceptibility to and severity of congenital heart diseases, notably ventricular septal defects and TOF, suggesting its potential as a biomarker of disease [148].…”
Section: Dnmts In Congenital Heart Defects and Paediatric Cvdmentioning
confidence: 99%
“…Previous studies have also investigated the role of DNMT SNPs in relation to the risk of CHDs. Lyu et al discovered that a SNP pair, including rs11892646 located in the DNMT3A gene and rs56219526 located in the MTRR gene, was associated with a risk of developing a conotruncal heart defect [147]. Further, a study in southeastern Iran found that the AG (heterozygous) genotype at rs6999593 in DNMT1 was strongly correlated with the susceptibility to and severity of congenital heart diseases, notably ventricular septal defects and TOF, suggesting its potential as a biomarker of disease [148].…”
Section: Dnmts In Congenital Heart Defects and Paediatric Cvdmentioning
confidence: 99%
“…A better understanding of the genes and pathways influencing progenitor cell behavior would improve our understanding of CTD etiology. A few studies have directly interrogated epistasis in the folate metabolism pathway as a risk factor for CTD [ 30 ], however to our knowledge, no CTD studies have performed a more comprehensive analysis of interaction across many genetic variants, genes, or pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital heart defects comprise some of the most common, serious, and clinically important groups/types of birth defects [ 1 , 2 , 3 ]. These defects consist of a heterogenous group of structural heart malformations (i.e., conotruncal heart defects that affect the cardiac outflow tract) that are thought to have at least some shared genetic basis [ 4 , 5 , 6 , 7 ]. Some conotruncal heart defects involve a deviation from the normal position of the origin of the aorta and pulmonary trunk, in which case the great vessels are said to be transposed.…”
Section: Introductionmentioning
confidence: 99%
“…In general, both common and rare inherited variants are thought to play a role in conotruncal defects [ 7 , 13 , 14 ]. However, prior genome-wide association studies (GWAS) of conotruncal heart defects, both among cases with and without 22q11.2DS, have had somewhat limited success in identifying significant associations.…”
Section: Introductionmentioning
confidence: 99%